The Role of Public Expenditure in Achieving The Goals of Economic Stability in Syria: An Analytical Study Relying on The Magic Square of Kaldor (2000-2021) (Damascus University Journal for the economic and Political sciences, 2026)
The study aimed to analyze the volume, structure, and key trends of public spending, as well as their implications on the four indicators of economic stability during the period of 2000-2021. These indicators include growth, unemployment, inflation, and the balance of trade, which constitute the four vertices of the Kaldor magic square.The study found that public expenditure exhibited a significant increase in its levels during the study period. Additionally, the proportion of current public expenditure compared to total public expenditure took the largest share, surpassing investment expenditure.The study also concluded that achieving the goals of Kaldor's magic square is not an easy task. While there was some improvement in certain dimensions of the magic square and a partial convergence towards optimality during the first period (2000-2010), there was a clear deterioration and distortion during the second period (2011-2021). This was evident from the noticeable narrowing of the magic square space.
Keywords: Public Spending; Economic Stability; Kaldor's Magic Square